Measurement of the ratio of the B0→D[star]-[tau]+[nu][tau] and B0→D[star]-[mu]+[nu][mu] branching fractions using three-prong [tau]-lepton decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; Han, Xiaoxue; et al. (Physical review letters, 2018)
The ratio of branching fractions R(D*−)≡B(B0→D*−τ+ντ)/B(B0→D*−μ+νμ) is measured using a data sample of proton-proton collisions collected with the LHCb detector at center-of-mass energies of 7 and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. For the first time, R(D*−) is determined using the τ-lepton decays with three charged pions in the final state. The B0→D*−τ+ντ yield is normalized to that of the B0→D*−π+π−π+ mode, providing a measurement of B(B0→D*−τ+ντ)/B(B0→D*−π+π−π+)=1.97±0.13±0.18, where the first uncertainty is statistical and the second systematic. The value of B(B0→D*−τ+ντ)=(1.42±0.094±0.129±0.054)% is obtained, where the third uncertainty is due to the limited knowledge of the branching fraction of the normalization mode. Using the well-measured branching fraction of the B0→D*−μ+νμ decay, a value of R(D*−)=0.291±0.019±0.026±0.013 is established, where the third uncertainty is due to the limited knowledge of the branching fractions of the normalization and B0→D*−μ+νμ modes. This measurement is in agreement with the standard model prediction and with previous results.
R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, M. De Cian, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere] (LHCb Collaboration)
Im Titel sind "star", "0" und "+" hochgestellt, bei "nu mu" ist "mu" tiefgestellt
Im Titel sind die Buchstaben star, tau, nu und mu als griechische Buchstaben dargestellt
Gesehen am 12.06.2019